IMPLIKASI ETIKA PANCASILA DALAM UPAYA PERLINDUNGAN HUTAN - Kania Uswama; Najicha, Fatma Ulfatun (Prodi PPKn Universitas Slamet Riyadi, 2023)
Pancasila contains five basic meanings that are interrelated with the nation's history, national ideology, ethics and various other aspects. Ethics is a system of values ​​or moral norms that serve as guidelines for a person or group of people to behave and act. The application of Pancasila in life can be said to be still not fully implemented. There are still various deviations from Pancasila values. Deviations that can still be seen clearly are forest fires. Various irresponsible human actions such as cutting down trees on a large scale and throwing cigarette butts carelessly are the causes of forest fires. The importance of forests for the survival of life is one of the important factors for the need for forest protection. Humans are required to have good ethics and are in harmony with the nation's ideology. Regarding this matter, Pancasila is emphasizing in the Preamble to the 1945 Constitution of the Republic of Indonesia as a guide, source of law, and legal principles in drafting laws and regulations regarding the environment, especially forests. Keywords: Pancasila, nation, ethics